Dampak Sertifikasi LSP Daarul Qur’an terhadap Peningkatan Kualitas Pengajaran Tahfizh di Pesantren Daarul Qur’an: The Impact of Daarul Qur'an LSP Certification on Improving the Quality of Tahfizh Teaching in Daarul Qur'an Islamic Boarding Schools - Tarmizi; Annur Fajri; Maryati (Al-Ma‘ani: Journal of Islamic Studies, 2026)
This study aims to analyze the impact of the certification program organized by the Daarul Qur’an Professional Certification Institute (LSP Daarul Qur’an) on improving the quality of Qur’anic memorization (tahfizh) teaching at Daarul Qur’an Islamic boarding schools. Teacher competence is a crucial factor in ensuring the quality of Qur’anic education. This research employed a descriptive quantitative approach by distributing questionnaires to 117 respondents consisting of teachers and students, selected using purposive sampling. Data were analyzed using SPSS. The findings indicate a highly positive perception of the certification program: 90.6% of respondents agreed that certification improves teachers’ Qur’anic recitation skills, 89.7% agreed it enhances pedagogical mastery, and 88.9% confirmed it encourages continuous competency improvement. Furthermore, certification strengthens institutional trust (88.0%) and enhances teaching effectiveness (84.6%) as well as improves teacher discipline (76,9%). Nevertheless, 86.4% of respondents expressed the need for post-certification training. The study concludes that LSP Daarul Qur’an certification effectively standardizes and improves the quality of tahfizh teaching, though its impact can be optimized through continuous professional development programs.